Implementasi Kontrol PID pada Mesin Pengembang Roti - Novianti Yuliarmas; Siti Aisyah; Handri Toar (Universitas Syiah Kuala, 2015)
Besides the ingredient composition, another important thing in the process of making dough is proofing, ie. dough rising process prior to roasting process. Proofing process requires a stable temperature to ensure that the dough is well rising. The purpose of this research is to make a proofing machine that uses DHT11 as a temperature sensor. Proportional-Integral-Derivative (PID) controller is implemented to guarantee that the machine remains at the temperature of 350Celcius, in which the fermentation process would success. PID control has been implemented in fluorescent lamp which been set its dim light to generate heat until it reach a predetermined set point value. The temperature was monitored using LCD and set to remain stable with the help of fan. The proofing process will last for 15 minutes which ended by the sound of the buzzer. The testing result shows that the value of , , will reach set point value within 120 seconds.